Genetic algorithm assisted fixed frequency sliding mode controller for quadratic boost converter in fuel cell vehicle. Issue 1 (1st March 2020) - Mukkapati, Ashok Bhupathi Kumar; Krishnasamy, Vijayakumar; Kaur, Rajvir
Abstract : This study presents the quadratic boost converter (QBC) as a power electronic interface between the fuel cell (FC) stack and the DC bus of the FC vehicle (FCV). QBC provides the high voltage gain to interface the low voltage, high current and non‐linear FC stack to higher voltage DC bus of the proposed architecture. The output voltage of FC is variable and is a function of cell chemistry, load variations and atmospheric conditions. Therefore, a genetic algorithm assisted fixed frequency sliding mode controller (SMC) based two‐loop control strategy is proposed and developed in this study. The accuracy of the control signal generated by the SMC depends on the accuracy of reference current generation. Therefore, genetic algorithm tuned proportional–integral controller is proposed to generate the ripple‐free reference current generation which follows the load‐side or source‐side variations. Further, a control algorithm is integrated with SMC which uses the design constants such that the chattering amplitude is suppressed and generates the control signal with fixed frequency. Consequently, the dynamic performance of the proposed controller is compared in terms of the tracking error, control effort and sliding surface error. The extensive studies are carried out under different dynamic conditions to analyse the robustness of the proposed controller for QBC‐based FCV.